Export intermediaries and adjustments to exchange rate movements - Stefano Bolatto; Marco Grazzi; Chiara Tomasi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
Building on a heterogeneous-firm model à la Melitz (2003), we propose a theory of intermediaries in international trade which rationalizes the available evidence on both aggregate and firm-level exports as well as their responsiveness to exchange rate movements. We introduce double marginalization for goods traded indirectly, i.e. through intermediaries, and local dis- tribution costs for all exporting firms, either intermediaries or direct exporters. This leads to heterogeneous markups, pricing-to-market and to a lower degree of exchange rate pass-through for goods exported by intermediaries. This result, validated on Italian firm-level trade data, is consistent with productivity sorting in the export mode and with the propensity of high productivity firms to absorb more exchange rate movements in their markups. We also explore how direct and intermediary export flows to a given destination react to exchange rate movements along the extensive margin of adjustment. Consistently with our theory, we find evidence of a larger variation in the overall number of varieties traded along the intermediary channel.
Keywords: F12; F14; D22; L22; 330; international trade; firms heterogeneity; intermediaries; export entry costs; local distribution costs; heterogeneous markups; product adding and dropping; exchange rate pass-through